Nitro derivatives and other constituents of Aristolochia melastoma - Nogueira, Cláudio R. [UNESP]; Lopes, Lucia Maria Xavier [UNESP] (Sociedade Brasileira de Química, 2012)
A phytochemical study of Aristolochia melastoma Manso has led to the isolation and identification of 20 known compounds, including aristolochic acids, sodium aristolochates, lignan, flavonoids, and nitro phenylethyl derivatives. Their structures were established by spectroscopic analysis. The presence of thalictricoside and secoisolariciresinol dimethyl ether diacetate is reported for the first time in the Aristolochiaceae family. In addition, the presence of nitro compounds in this species is significant.
Keywords: Aristolochia melastoma; aristolochic acid; nitro phenylethyl derivative